Peran Literasi Keuangan Dalam Memoderasi Pengaruh Effort Expectancy, Pengaruh Sosial, dan Performance Expectancy Terhadap Penggunaan Sistem Pembayaran Non-Tunai (Studi Kasus Mahasiswa Akuntansi Kota Semarang) - Erni Dewi Fitriani; Hardiwinoto Hardiwinoto; Fatmasari Sukesti (Jurnal Akuntansi Manajerial, 2026)
This study aims to analyze the influence of Effort Expectancy, Social Influence, and Performance Expectancy on the use of non-cash payment systems, as well as the role of Financial Literacy as a moderating variable. The background of this study is the rapid development of financial technology (fintech) in Indonesia, which has driven a significant increase in electronic money transactions. Using a quantitative approach and the Moderated Regression Analysis (MRA) method, data were collected through questionnaires from 396 undergraduate Accounting students in Semarang City. Data analysis used the SPSS Statistics 26 program. The results showed that Effort Expectancy, Social Influence, and Performance Expectancy had a positive and significant influence on the use of non-cash payment systems. However, Financial Literacy was found to be unable to moderate the relationship between the three variables and system usage. This indicates that ease of use, social encouragement, and practical benefits are more dominant in driving technology adoption than the level of user financial literacy. These results provide insights for service providers to focus on the aspects of ease and practical benefits in their product development strategies.